Death in a Carbon Dioxide Therapy Bath: A Case Report and Review of the Literature. Issue 1 (March 2019) - Samuel, Julian; Georgievskaya, Zhanna
Carbon dioxide (CO2 ) therapy is the subcutaneous or transcutaneous administration of CO2 for therapeutic purposes. Carbon dioxide therapy is used for localized lipolysis, to treat chronic skin conditions, and is a safe treatment. Full-body CO2 baths are offered in European spa centers, in which the clients are placed into full body bags infused with CO2 at an optimal concentration range between 1000 and 1400 mg/L (516 000-722 500 ppm). Commercially manufactured, air-tight bags and accompanying apparatus designed to provide CO2 baths can be purchased for home use. Few human CO2 -related deaths have been reported. They have been mostly accidental, consisting of persons trapped in a closed environment in the presence of "dry ice" or solid CO2 . There have been no reported deaths of a human undergoing a CO2 therapy at home. We present a case of a middle-aged male found at home completely inside an air-sealed bag wrapped tightly around his body. The bag was connected to a working pump and a CO2 gas tank. The pump was connected through an inflow and outflow circuit to the bag. The inflow tubing for CO2 gas delivery was partially disrupted, while the outflow tubing was intact. The autopsy and toxicology were unremarkable. The cause of death was determined to be asphyxia by vitiated atmosphere as evident by the displacement of oxygen by CO2 and low pressure created inside a "CO2 therapy bath." The manner of death was accidental.